2021
DOI: 10.7759/cureus.15065
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Induced Sinus Bradycardia

Abstract: Steroids are one of the most commonly used drugs and known to be associated with several side effects. There have been case reports about the associated sinus bradycardia with pulse dose corticosteroids administration both IV and oral. We present a case of asymptomatic sinus bradycardia associated with oral prednisone 40 mg. A 69-year-old male was admitted to the ICU for sepsis and subsequently was found to have gastrointestinal (GI) bleed. He developed an acute gout attack during hospitalization and was treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…A literature review revealed that steroid-induced bradycardia is likely underdiagnosed because most patients are asymptomatic,2 7 8 in contrast to our case where the patient experienced symptoms. Although the bradycardia resolves spontaneously after discontinuation of the medication, it is also crucial to rule out other, more prevalent causes of bradycardia, such as hypothyroidism, electrolyte imbalance and the use of drugs including beta-blockers, calcium channel blockers and digitalis.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…A literature review revealed that steroid-induced bradycardia is likely underdiagnosed because most patients are asymptomatic,2 7 8 in contrast to our case where the patient experienced symptoms. Although the bradycardia resolves spontaneously after discontinuation of the medication, it is also crucial to rule out other, more prevalent causes of bradycardia, such as hypothyroidism, electrolyte imbalance and the use of drugs including beta-blockers, calcium channel blockers and digitalis.…”
Section: Discussioncontrasting
confidence: 68%
“…Although steroid therapy’s more common side effects are hyperglycaemia, electrolyte abnormalities, hypertension, osteoporosis and gastritis, physicians need to be aware of the cardiovascular side effects of short-term steroids. Researchers have described changes in blood pressure, heart rate, cardiac dysrhythmias and even death in patients receiving short-term intravenous steroids 2 3…”
Section: Introductionmentioning
confidence: 99%
“…It is usually benign in nature and asymptomatic. [ 8 ] Our patient was also clinically and hemodynamically stable. Common symptoms of bradycardia include dizziness, chest pain, fatigability, and syncope.…”
Section: Discussionmentioning
confidence: 61%
“…COVID-19-induced bradyarrhythmia was reported ( 7 , 8 ), in addition to it, the many nonspecific bradycardia cases in patients without cardiovascular risk factors was also observed. Several reports have suggested that medications for COVID-19, such as remdesivir ( 9 - 14 ) or steroids ( 15 ), may be associated with the incidence of bradycardia; whereas bradycardia may also be linked to the SARS-CoV-2 infection itself, as previously reported in cases of influenza infection ( 16 ). To further understand the pathophysiology behind bradycardia in COVID-19, we evaluated whether the incidence rate of bradycardia in patients with COVID-19 was higher than that in patients with influenza and COVID-19.…”
Section: Introductionmentioning
confidence: 83%